1997
DOI: 10.1007/bf02358002
|View full text |Cite
|
Sign up to set email alerts
|

Leaf effects of wild species ofSolanum and interspecific hybrids on growth and behaviour of the potato tuber moth,Phthorimaea operculella Zeller

Abstract: SummaryFour introductions of Sohmum berthaultii wild species and seven S. tuberosumxS, berthaultii hybrids were evaluated by antibiosis and antixenosis laboratory tests with potato tuber moth. Some morphological and chemical traits related to the trichomes were analysed. Two clones of the wild species S. spalwipilum and five of S. pinnatisectum, characterised by high tuber resistance, were tested for leaf resistance, both by antibiosis and antixenosis assays. The genotypes with high density of trichomes A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
0
18
1
5
Order By: Relevance
“…Host plant resistance studies have shown that there are some resistance mechanisms in the foliage and tubers of the potato cultivars (Brown 2007). Musmeci et al (1997) reported some foliar resistance on wild potatoes and interspecific hybrids. Das et al (1993) observed that tuber nutritional quality is an important resistance factor limiting normal growth and development of P. operculella larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Host plant resistance studies have shown that there are some resistance mechanisms in the foliage and tubers of the potato cultivars (Brown 2007). Musmeci et al (1997) reported some foliar resistance on wild potatoes and interspecific hybrids. Das et al (1993) observed that tuber nutritional quality is an important resistance factor limiting normal growth and development of P. operculella larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Despite gelechiid larvae causing most damage to tubers, and often severe damage in potato storage facilities, the mechanisms of resistance in potato foliage are considerably better understood than resistance mechanisms in tuber (Gurr 1995;Musmeci et al 1997;Tingey 1999, 2000). Furthermore, good progress has been made in breeding for resistance to above-ground damage through introgression with trichome-bearing wild potato species (Plais- On dead potato leaves and in the soil close to host plant in the field; On tubers in storage (Traynier 1975;Das et al 1993aDas et al , 1993b Often greater fitness on potato tubers compared to foliage, will also feed on tomato, eggplant and other Solanaceous crops (Traynier 1975;Raman and Palacios 1982) Damage to shallow and exposed tubers particularly in irrigated fields of warm regions; Severe damage to stored potatoes in cooler Andean regions ( On above-ground foliage (Pereyra and Sanchez 2006) Tomato preferred over potato, not known to feed on tubers, feeds on a variety of other Solanaceous crops and wild plants (Pereyra and Sanchez 2006) Mines leaves, fruits, flowers, buds, and stems (Pereyra and Sanchez 2006) ted et Malakar and Tingey 1999).…”
Section: Foliage Resistancementioning
confidence: 99%
“…Optimum oviposition substrates for P. operculella include rough surfaces (with surface depressions large enough to accommodate the eggs), but hairy surfaces also stimulate oviposition (Traynier 1975;Fenemore 1978). In comparative studies with foliage from a range of potential host plants, leaf hairs have been associated with increased egg-laying by P. operculella directly on the leaf surface (Gurr 1995;Horgan et al 2007a), whereas glandular trichomes reduced the proportion of eggs laid directly on the plants (Musmeci et al 1997;Tingey 1999, 2000;Gurr and McGrath 2002;Horgan et al 2007a). Similarly, unidentified compounds in hexane leaf extracts of Lycopersicon hirsulutum f. typicum (LA 1777), and associated glandular trichomes, appear to deter egg-laying by T. absoluta, a species which does not lay eggs in the soil (Ecole et al 2001).…”
Section: Fitness Reductions Related To Hexane Leaf Extracts Ecole Etmentioning
confidence: 99%
See 2 more Smart Citations